Atrial fibrillation in pregnancy: a growing challenge. (3rd August 2017) - Katsi, Vasiliki; Georgiopoulos, Georgios; Marketou, Maria; Oikonomou, Dimitrios; Parthenakis, Fragiskos; Makris, Thomas; Nihoyannopoulos, Petros; Vardas, P.; Tousoulis, Dimitris
Abstract: Background: Atrial fibrillation (AF) constitutes a relatively infrequent pregnancy complication, which may be a therapeutic Gordian knot. Indeed, sparse data exist regarding the prevalence, prognosis, and management of AF during pregnancy. In general, AF occurs as a benign, self-limited arrhythmia, but occasionally may have severe hemodynamic consequences in pregnant patients suffering from heart failure, congenital heart disease, or other comorbidities. Extra-cardiac causes of AF should always be meticulously excluded. Review: Treatment decisions are difficult, since medications may cross the placental barrier and potentially affect fetal growth and organogenesis, or even result in fetal bradyarrhythmias. Treatment goals are not differentiated in comparison to those regarding AF occurring in the general population. Still, while maternal treatment is prioritized, issues regarding fetal health must deliberately be considered. Consequently, hemodynamic instability is to be promptly treated with synchronized electrical cardioversion. In contrast, in stable patients, pharmacologic cardioversion, under appropriate antithrombotic regimen, should be attempted. Selection of appropriate antithrombotic therapy, including novel oral anticoagulants, imposes further difficulties on therapeutic decision-making. Further clinical trials are warranted in order to assess the pathophysiology and prognosis of AF in pregnancy and ameliorate the evidence-based therapeutic strategy in this specific group of the population.